Dual compartmental targeting of cell cycle and angiogenic kinases in colorectal cancer models. Issue 9 (October 2018) - Capasso, Anna; Pitts, Todd M.; Klauck, Peter J.; Bagby, Stacey M.; Westbrook, Lindsey; Kaplan, Jeffrey; Soleimani, Milad; Spreafico, Anna; Tentler, John J.; Diamond, Jennifer R.; Arcaroli, John J.; Messersmith, Wells A.; et al.
Abstract : Cancer is a disease caused by several factors characterized by uncontrolled cell division, growth, and survival. ENMD-2076, is a novel orally active small molecule multikinase inhibitor targeting angiogenesis, proliferation, and the cell cycle. It is selectively active against the mitotic kinases aurora A and B, and kinases responsible for angiogenesis including VEGFR2/KDR and FGFR1 and 2. ENMD-2076 has been shown to inhibit tumor growth and prevent angiogenesis in vitro and in vivo in preclinical cancer models. Moreover, in a phase I trial, ENMD-2076 was well tolerated, exhibited a linear pharmacokinetic profile, and showed a promising antitumor activity in a number of solid tumors. In this study, we show that ENMD-2076 has antiproliferative effects, causes cell cycle arrest, and has activity in preclinical models of colorectal cancer (CRC), including patient-derived xenograft (PDX) models. Forty-seven human CRC cell lines were exposed in vitro to ENMD-2076 and analyzed for effects on cell cycle, apoptosis, and downstream effector proteins. The drug was then tested against 20 human CRC PDX models to further evaluate in-vivo antitumor activity. We show that ENMD-2076 exhibits a broad range of activity against a large panel of CRC cell lines with varying molecular characteristics. Mechanistically, ENMD-2076 exposure resulted in a G2/M cell cycle arrest, an increase in aneuploidy, and cell death in responsive cell lines. In addition, ENMD-2076 treatment resulted in a promising antitumor activity in CRC PDX models. These results support the continued development of ENMD-2076 in CRC including further exploration of rational combinations. Abstract : Supplemental Digital Content is available in the text.